The Impact of the Global Food Crisis and Indonesia's Strategies For Achieving Food Security - Muhammad RIDWAN; Suranto SURANTO (International Journal of Environmental, Sustainability, and Social Science, 2025)
The world food crisis, triggered by various factors such as climate change, geopolitical conflicts, and a global pandemic, has had significant impacts on food security in various countries, including Indonesia. This article aims to identify and analyze sustainable strategies that can be implemented to address the impacts of the global food crisis on Indonesian food security and achieve food self-sufficiency. This research uses a qualitative descriptive method with a literature review approach using relevant sources. The research results indicate that sustainable strategy efforts to achieve national food security and food self-sufficiency include: (1) Increasing the productivity of agricultural food commodity, (2) Expansion of agricultural areas, (3) Diversification of local carbohydrate food sources, (4) Optimizing marine resource, (5) Community empowerment, and (6) Policy support and holistic cooperation. Overall, national food security can be achieved through a holistic socio-economic approach involving various aspects, from stakeholders, academia, and society.